A 4‐microRNA signature for survival prognosis in pediatric and adolescent acute myeloid leukemia. Issue 3 (22nd September 2018) - Zhu, Ruiqi; Lin, Wenyi; Zhao, Weiwei; Fan, Fengjuan; Tang, Liang; Hu, Yu
Abstract: Acute myeloid leukemia (AML) is a hematologic malignancy with significant molecular heterogeneity. MicroRNAs (miRNAs) play a critical role in AML diagnosis, pathogenesis, and prognosis of AML. Little has been done to identify a miRNA signature in pediatric and adolescent patients for predicting overall survival. This study aims to identify a panel of miRNA signature that could predict the prognosis of all younger AML patients with all subtypes of AML by analyzing data from The Cancer Genome Atlas (TCGA). A total of 229 patients under 23 years with miRNA data and corresponding clinical data from TCGA database were enrolled in this study. Through conducting multivariate analysis in the training test, it was identified that the high expression of hsa‐miR‐509 and hsa‐miR‐542 were independent poor prognostic factors, whereas that of hsa‐miR‐146a and hsa‐miR‐3667 had a trend to be favorable factors. A 4‐miRNA signature was constructed by these miRNAs considering the weight of each. In testing group and all 229 patients' cohort as well as 59 cytogenetically normal AML (CN‐AML) patients' cohort, higher risk score was associated with shorter overall survival (OS). All results were confidential by using powerful statistical analysis. Gene ontology and Kyoto Encyclopedia of Genes and Genomes analysis were carried out to further develop leukemia‐relevant mechanisms supporting the model. The results indicate that the 4‐miRNA‐based signature is a reliable prognostic biomarker for pediatric and adolescent AML patients. Abstract : Our study identified a 4‐microRNA (miRNA) signature as potential prognostic predictor for pediatric and adolescent acute myeloid leukemia (AML) patients using The Cancer Genome Atlas TARGET‐AML data set. Further studies and functional investigations are required to explore the underlying mechanisms of these miRNAs in signature.